Anti-social Parental Behaviour, Problematic Parenting and Aggressive Offspring Behaviour during Adulthood: A 25-Year Longitudinal Investigation - Brook, Judith S.; Kasen, Stepahnie (The British journal of criminology, 2004)
Data from a 25-year community-based prospective longitudinal study were used to investigate the role of problematic parenting in the association between a history of anti-social parental behaviour and subsequent offspring aggression during adulthood. Parents with a history of anti-social behaviour were significantly more likely than other parents were to engage in two or more types of problematic child-rearing behaviour. Problematic parenting was associated with offspring aggression during adulthood after a history of anti-social parental behaviour was controlled statistically. Anti-social parental behaviour was associated with aggressive offspring behaviour during adulthood before, but not after, problematic parenting was controlled. These findings support the hypothesis that problematic parenting tends to mediate the association between anti-social parental behaviour and subsequent offspring aggression